Academic Staff Perspectives on the Impact of Artificial Intelligence on Pharmaceutical Sciences Research and Writing: A Qualitative Study. - Mohammed, Samer Imad; Jabbar Kadhim, Dheyaa; Zuheir Al-Metwali, Basma; Mudher Mikhael , Ehab; Mohammed Hassan, Noor (Iraqi Journal of Pharmaceutical Sciences, 2025)
Artificial intelligence (AI) offers significant benefits to biomedical research and academic writing. Nevertheless, using AI-powered writing aid tools has prompted worries about excessive dependence on these tools and their possible influence on writing proficiency. The current study aimed to explore the academic staff’s perspectives on the impact of AI on academic writing.This qualitative study incorporated in-person interviews with academic faculty members. The interviews were conducted in a semi-structured manner, using a predetermined interview guide consisting of open-ended questions. The interviews were done in person with the participants from May to November 2023. The data was analyzed using thematic analysis.Ten academics aged 41 to 59 years participated in this study. The majority had assistant professor degrees. Most of the participants did not trust the ability of AI to write an accurate scientific article because it can provide inaccurate results and/or improper citations. Regarding the concerns about the usage of AI in academic writing, most participants had negative perceptions, and they believed that AI would diminish students' writing skills. Most participants reported the impossibility of AI being the sole author of scientific articles; instead, it can just support humans in academic writing. Students could use AI to obtain scientific information, get some research ideas, improve writing by reducing grammatical errors, and save students time in writing. To get benefits from AI in academic writing, The faculty members agreed on the necessity of issuing legislation about the usage of AI by the Ministry of Higher Education or the University. Additionally, all agreed on the necessity of conducting workshops to teach staff about AI.Finally, we can conclude that AI could potentially play a beneficial role in academic writing. However, most academic faculty express concerns about their students relying only on these tools, which may result in dependency and a decline in writing proficiency. It is crucial to develop regulations and conduct workshops to educate staff about AI and its utilization by the Ministry of Higher Education or the University.